Preventive Measures to Eliminate Asbestos-Related Diseases in Singapore - John Wah Lim; David Koh; Judy Sng Gek Khim; Giang Vinh Le; Ken Takahashi (Elsevier, 2011)
The incidence of asbestos-related diseases (ARD) has increased in the last four decades. In view of the historical use of asbestos in Singapore since the country started banning it in phases in 1989 and the long latency of the disease, the incidence of ARD can be expected to increase further. As occupational exposure to asbestos still occurs, preventive measures to eliminate ARD continue to be required to protect the health of both workers and the public from asbestos exposure. The majority of occupational exposures to asbestos at present occur during the removal of old buildings. Preventive measures have been utilized by different government ministries and agencies in eliminating ARD in Singapore over the past 40 years. These measures have included the enforcement of legislation, substitution with safer materials, and engineering controls during asbestos removal as well as improvements in personal hygiene and the use of personal protective equipment. The existing Workman's Compensation System for ARD should be further refined, given that is currently stipulates that claims for asbestosis and malignant mesothelioma be made within 36 and 12 months after ceasing employment.